The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1029/2019jd030765
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Near‐Surface NO2 Pollution With Pandora Total Column NO2 During the Korea‐United States Ocean Color (KORUS OC) Campaign

Abstract: Near‐surface air quality (AQ) observations over coastal waters are scarce, a situation that limits our capacity to monitor pollution events at land‐water interfaces. Satellite measurements of total column (TC) nitrogen dioxide (NO2) observations are a useful proxy for combustion sources, but the once daily snapshots available from most sensors are insufficient for tracking the diurnal evolution and transport of pollution. Ground‐based remote sensors like the Pandora Spectrometer Instrument (PSI) that have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 57 publications
(103 reference statements)
1
32
0
Order By: Relevance
“…A high-resolution version of the MIROC-Chem model, with a horizontal resolution of T106 (1.1° x 1.1°) and 32 hybrid (eta) vertical levels, MIROC-Chem-H (Sekiya et al, 2018), was also used. This model utilizes the same chemical and transport module as the MIROC-Chem (c.f., Section 2.2.3) and has been used to study processes controlling air quality in east Asia during the KORUS-AQ aircraft campaign (Miyazaki et al, 2019;Thompson et al, 2019) and conduct the second tropospheric chemical reanalysis Miyazaki et al,in prep) for 2005-2018. Kanaya et al (2019) demonstrated the overall good performance of the ozone and CO analyses in TCR-2 over remote oceans using observations from research vessels.…”
Section: Miroc-chem-hmentioning
confidence: 99%
“…A high-resolution version of the MIROC-Chem model, with a horizontal resolution of T106 (1.1° x 1.1°) and 32 hybrid (eta) vertical levels, MIROC-Chem-H (Sekiya et al, 2018), was also used. This model utilizes the same chemical and transport module as the MIROC-Chem (c.f., Section 2.2.3) and has been used to study processes controlling air quality in east Asia during the KORUS-AQ aircraft campaign (Miyazaki et al, 2019;Thompson et al, 2019) and conduct the second tropospheric chemical reanalysis Miyazaki et al,in prep) for 2005-2018. Kanaya et al (2019) demonstrated the overall good performance of the ozone and CO analyses in TCR-2 over remote oceans using observations from research vessels.…”
Section: Miroc-chem-hmentioning
confidence: 99%
“…Chandra, 2003, Inness et al, 2015). Other processes that potentially influence tropospheric ozone, which are generally considered of minor importance, are the Quasi-biennial Oscillation (Neu et al, 2014) and the North Atlantic Oscillation (Thouret et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An updated CTM and satellite retrievals are used in TCR-2 (Kanaya et al, 2019;Miyazaki et al, 2019aMiyazaki et al, , 2019bThompson et al, 2019). A high-resolution version of the MIROC-Chem model with a horizontal resolution of T106 (1.1° x 1.1°) was used.…”
Section: Updated Tropospheric Chemistry Reanalysis (Tcr-2)mentioning
confidence: 99%
“…Kanaya et al (2019) demonstrated the TCR-2 ozone and CO performance using research vessel observations over open oceans. Thompson et al (2019) used the TCR-2 data to help understanding of near surface NO 2 pollutions observed during the KORUS-OC campaign. Both for TCR-1 and TCR-2 the reanalysis data is archived on a twohourly output frequency.…”
Section: Updated Tropospheric Chemistry Reanalysis (Tcr-2)mentioning
confidence: 99%
See 1 more Smart Citation